Incidence trends for upper aerodigestive tract cancers in rural United States counties. Issue 8 (7th March 2019) - Pagedar, Nitin A.; Kahl, Amanda R.; Tasche, Kendall K.; Seaman, Aaron T.; Christensen, Alan J.; Howren, M. Bryant; Charlton, Mary E.
Abstract: Background: Recent declines in cancer incidence and mortality have not been distributed equally across the United States. Factors such as tobacco cessation and human papillomavirus presence might differentially affect urban and rural portions of the country. Methods: We used the Surveillance, Epidemiology, and End Results database to assess cancer incidence rates and trends from 1973 to 2015. We compared incidence rates for oral cavity, oropharynx, and larynx cancer in urban and rural counties and identified trends using Joinpoint software. Results: Incidence of larynx and oral cavity cancer are decreasing faster in urban areas than in rural areas, while incidence of oropharynx cancer is increasing faster in rural areas than urban areas. Conclusions: Relative trends in incidence of larynx, oral cavity, and oropharynx cancer over the past 40 years are unfavorable for rural United States counties compared with urban areas. Cancer control programs should take this into account.